Addisonian hyperpigmentation in a case of late onset familial glucocorticoid deficiency and dramatic improvement with glucocorticoid supplementation - Sunanda Mahajan; Siddhi Chikhalkar; S Rajasekar (Wolters Kluwer Medknow Publications, 2020)
Addison's disease is a chronic endocrine disorder in which the adrenal glands do not produce enough steroid hormones mostly both glucocorticoid and mineralocorticoid. Most common causes of primary adrenal insufficiency are due to autoimmune adrenalitis in developed world, and tuberculosis in developing world. Here we present a rare case of primary adrenal insufficiency with addisonian pigmentation secondary to familial glucocorticoid deficiency.